Prada & prejudice - Hubbard, Amanda (New York : Razorbill, 2009)
While on a trip to London, Callie buys a pair of genuine Prada pumps that magically transport her to the early nineteenth-century, where Callie meets Emily, who helps her adapt to her new surroundings and win the heart of the handsome Duke of Harksbury, who may be Callie's ticket back to the future.
Booklist
Publisher's Weekly
School Library Journal
Young Adult.
Young Adult
Keywords: Self-confidence -- Fiction; Time travel -- Fiction; Self-confidence -- Fiction; Time travel -- Fiction; England -- Social life and customs -- 19th century -- Fiction; England -- Social life and customs -- Fiction